Frontolimbic atrophy is associated with agitation and aggression in mild cognitive impairment and Alzheimer's disease. (18th December 2012) - Trzepacz, Paula T.; Yu, Peng; Bhamidipati, Phani K.; Willis, Brian; Forrester, Tammy; Tabas, Linda; Schwarz, Adam J.; Saykin, Andrew J.; ,
Abstract : Background: The neuroanatomy of agitation and aggression in Alzheimer's disease is not well understood. Methods: We analyzed 24 months of Alzheimer's Disease Neuroimaging Initiative data for patients with Alzheimer's disease, mild cognitive impairment‐stable, and mild cognitive impairment‐converter (n = 462) using the Neuropsychiatric Inventory Questionnaire Agitation and Aggression subscale. Magnetic resonance imaging regions of interest that correlated with Neuropsychiatric Inventory Questionnaire Agitation and Aggression subscale raw scores were included in mixed‐model, repeated‐measures analyses of agitation and aggression over time with age, sex, apolipoprotein E ε4 status, education, and Mini‐Mental State Examination score as covariates. Results: Neuropsychiatric Inventory Questionnaire Agitation and Aggression subscale scores worsened in patients with Alzheimer's disease and in mild cognitive impairment‐converter ( P < .05; trend for mild cognitive impairment, P = .0518). Greater agitation and aggression severity was associated with greater atrophy of frontal, insular, amygdala, cingulate, and hippocampal regions of interest ( P < .05). Mini‐Mental State Examination score was significant in mixed‐effect model repeated measures only in mild cognitive impairment‐converters for posterior regions of interest. Demographics and apolipoprotein ε4 were not associated with agitation and aggression. Conclusions: Agitation and aggression in Alzheimer's disease and mild cognitive impairment is associated with neurodegeneration affecting the anterior salience network that may reduce capacity to process and regulate behaviors properly.